Mapping Terra Incognita: An Expert Elicitation of Women's Roles in Wildlife Trafficking - Agu, Helen U.; Andrew, Cydney; Gore, Meredith L. (Frontiers in Conservation Science, 2021)
Abstract The gendered dimensions of wildlife trafficking remain understudied even though the problem is of great socio-environmental significance. Data about the roles of women in wildlife trafficking offer critically needed indicators that can contribute to building evidence and setting targets for, and monitoring progress of, sustainable and equitable futures. We set three objectives for this research filling a major gap in conservation knowledge: (1) explore expert perceptions of primary roles that women may play in wildlife trafficking, (2) explore expert perceptions of secondary roles that women may play in wildlife trafficking, and (3) explore variability in roles for women in wildlife trafficking. We used an online survey to conduct expert elicitation in February 2020 to achieve objectives. Experts (N= 215) identified key assumptions associated with six primary and 32 secondary roles for women in wildlife trafficking. Results highlight the impacts of wildlife trafficking manifest in varied contexts across society, including persons harmed at local levels such as family members in general, widows and orphans. The perceived roles of women in the wildlife trafficking networks can be factored into transformative solutions to help combat wildlife trafficking and data from expert elicitation can inform future hypotheses and inferences on this topic of broad socio-environmental significance. Keywords: corruption, environmental law, gender, gender-environment nexus, Sustainable Development Goals, wildlife crime